Filament fabrication and fdm 3D printing of pla/biopbs-based composite materials for advanced sustainable manufacturing applications - Daminabo, Samuel I. C. (Cranfield University, 2023)
With the limited range of commercially viable biobased and biodegradable filament materials available for fused deposition modelling (FDM)-based additive manufacturing (AM), this work aims to advance the knowledge and potential of sustainable polymer-based materials for 3D printing (3DP) applications. This work investigates polymer phase changes in 80 wt.% poly lactic acid (PLA)/20 wt.% biobased polybutylene succinate (BioPBS)-based blends after a direct or two-step filament fabrication process. 3DP filaments made of 80 wt.% PLA /20 wt.% BioPBS blends and their nanocomposites containing either hydrophilic bentonite nano clay (HbnC) or reduced graphene oxide (rGO) at 1 part per hundred resins (phr) are compared for polymer phase properties and rheological behaviour. Subsequently, ‘Power law’ and ‘Arrhenius’ models are combined to develop complex viscosity master-curves as a predictive model for each material formulation; while each fabricated filament is applied with developed 3D printing strategies to produce tensile and interlayer-bond test materials. Findings show that between the two filament fabrication methods, the multi-step filament fabrication route causes a higher PLA phase crystallinity of about 27%. However, the multi-step processing route and inclusion of rGO in the PLA80/BioPBS20 material matrix increases PLA crystallinity to about 34%. Moreover, rGO is found to limit the recrystallization of the BioPBS phase. Furthermore, following a successful development of complex viscosity master curve models for PLA80/BioPBS20-based formulations, tensile-fractured 3D- printed parts were also found to show an improved compatibilization of the immiscible PLA and BioPBS phases upon addition of either nanomaterial, hence offering a promising outlook for the use of PLA80/BioPBS20-based materials for sustainable and multifunctional part productions.
Keywords: 3D printing; biocomposites; melt-processing; crystallinity; viscosity; tensile; mechanical; multifunctional